Pembangunan Aplikasi WA Gateway Desa Barusjahe Kecamatatan Barus Jahe Kabupaten Karo - Kris Diansen (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The current challenge is how to provide fast, accurate, and targeted information to the public. In the context of village government, information delivery is often still done manually, such as through direct announcements, circulars, or word of mouth. This method is certainly more time-consuming and has the potential to lead to misunderstandings. Therefore, a system is needed that can deliver information efficiently, especially to the community who have an interest in it. The appropriate goal is to ensure that the public receives information only those who align with the category or need of the message being conveyed, thereby preventing the dissemination of irrelevant information. Implementing a mass messaging application using the WhatsApp Gateway system can be an effective solution for Barusjahe Village. By utilizing this technology, village officials can send important information such as activity announcements, administrative notices, service schedules, and emergency information quickly and simultaneously. This system also allows for grouping community data by hamlet, type of interest, or specific category so that messages can be sent in a more targeted manner. Barusjahe Village, with its large population and four hamlets, should utilize information technology to improve the quality of public services. Furthermore, system access rights can be designed to avoid overlapping between users. This ensures data security and consistency. Each admin or operator can only access and manage data within their authority. Through the implementation of this application, it is hoped that the information delivery process in villages will become more modern, efficient, transparent, and targeted.